PENGARUH PENDIDIKAN DAN KOMPETENSI TERHADAP PRODUKTIVITAS PEMUDA KOTA PAYAKUMBUH DENGAN JIWA KEWIRAUSAHAAN SEBAGAI VARIABEL MODERASI - Apripeli, Yolanda; Putri, Anne (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Productivity is an important part that must be considered because it describes the economic growth of a country/region. Increasing productivity will encourage a country or region to become more competitive, with effective and efficient production levels, as well as a productive workforce. This research aims to analyze the influence of education and competence on youth productivity withentrepreneurial spirit as a moderating variable. The population in this study were youth who worked in Payakumbuh City. This research uses quantitative methods with primary data in the form of a questionnaire with a total research sample of 70 respondents taken based on purposive sampling techniques. The data analysis technique used is descriptive analysis and inferential statistical analysis with Structural Equation Modeling (SEM) analysis of various Partial Least Square (PLS) variants. Measurement model or outer model, structural model test or inner model, and hypothesis testing with the help of Smart-PLS 4.0 software as a testing tool. The results of this research show that education and competence have no effect on youth productivity. Meanwhile, entrepreneurial spirit significantly weakens the relationship between education and youth productivity and entrepreneurial spirit significantly strengthens the relationship between competence and youth productivity. Keywords: Education, Competence, Entrepreneurial Spirit, Youth Productivity